Part of boundary wall around the temple - Temples of India Project Team (Jio Institute, 2024)
The broken fragments of the temple, including the vedibandha mouldings, are placed close to each other to form a boundary wall around the temple. Some of the mouldings are carved with the figures of deities, females and couples. Fragments of pillars can also be seen.